TERAPI MUZIK SEBAGAI RAWATAN KOMPLEMENTARI DI BIMARASTAN AL-MANSURI PADA ABAD KE 13 MASIHI (Music Therapy as a Complementary Treatment in Bimarastan al-Mansuri during the 13th Century) - Abdullah, Mohd Jailani; Sidik @ Mat Sidek, Roziah; Kamaruzaman, Azmul Fahimi (Journal of Al-Tamaddun, 2019)
Music therapy is widely used as a treatment in most hospitals of the Medieval Islamic Civilization, one of which is Bimarastan al-Mansuri Egypt Cairo. Music therapy in this hospital is performed by a group of musicians who are given a monthly salary as provided by waqaf documents. Nevertheless, the waqaf document of this hospital, does not state explicitly the type of patient being treated and the status of music therapy as a treatment, either conventional or complementary. Therefore, this article will cover the music therapy application in Bimarastan al-Mansuri in the scope of the treated patient type and also the treatment status of music therapy based on the information obtained from the works of history and travelog. This study uses qualitative methodology and literature study method by analyzing various primary and secondary sources. The findings show that Bimarastan al-Mansuri applies music therapy through instruments and songs directly to patients who are in the rehabilitation room and insomnia patients placed in a special room. It is also indirectly applied to other patients in ward such as orthopedic ward and mental patient ward through the flow of water, instruments and songs (heard from the rehabilitation room and insomnia room) and also the voice of azan and al- Qur'an recitation. The music therapy treatment in this hospital is intended to calm down, reduce the symptoms or pain and assist the patient's recovery process. Thus, it is proven that music therapy in Bimarastan al-Mansuri as a complementary treatment adjunct to conventional medicine, which uses of medication and surgery.